Effects of hydrolyzed collagen supplementation for Skin Anti-Aging - Anna Gliwa; Marek Kurowski; Karolina Kuczapska; Monika Ryglewicz; Dariusz Fabian; Elbieta Leszczynska-Knaga; Natalia Jakubczyk; Weronika Rutkowska-Kawalec; Paweł Moczydłowski; Karolina Michhalczuk (Quality in Sport)
In an era of an aging population with the rise of social media, both men and women are paying more and more attention to the healthy appearance of their skin and overall health.